Consuming Salak Sidimpuan (Salacca sumatrana Becc.) Juice during strenuous physical activity reduced levels of creatine kinase and lactate dehydrogenase in white male rats - Siregar, Nurhamida Sari (Philippine Journal of Science, 2023)
Strenuous physical activity may result in physical harm, as indicated by increased blood parameters like creatine kinase (CK) and lactate dehydrogenase (LDH). However, one effective way to prevent this damage before exercising is by consuming easily digestible foods such as salak sidimpuan juice. This study explored the effects of salak sidimpuan juice on CK and LDH levels during strenuous physical activity. The study utilized an experimental design with a post-test control design involving 24 white male rats divided into four groups: negative control, treatment group 1 (T1), treatment group 2 (T2), and treatment group 3 (T3). The negative control group underwent strenuous physical activity, whereas the treatment groups underwent the same training with the addition of different amounts of salak juice (1, 2, and 3 mL). The study was conducted for 4 wk in the USU Pharmacy Laboratory, and the results conclusively demonstrated that consuming salak sidimpuan juice during strenuous physical activity significantly reduced CK and LDH levels in experimental animals. Moreover, the study found that the more salak sidimpuan juice consumed during exercise, the more significantly decreased CK and LDH levels in experimental animals. Therefore, it can be concluded that consuming salak juice during strenuous physical activity can effectively reduce CK and LDH levels in experimental animal.